Nivolumab alone or in combination with cisplatin plus gemcitabine in Japanese patients with unresectable or recurrent biliary tract cancer: a non-randomised, multicentre, open-label, phase 1 study. (August 2019) - Ueno, Makoto; Ikeda, Masafumi; Morizane, Chigusa; Kobayashi, Satoshi; Ohno, Izumi; Kondo, Shunsuke; Okano, Naohiro; Kimura, Keisuke; Asada, Suguru; Namba, Yoshinobu; Okusaka, Takuji; Furuse, Junji
Summary: Background: This study aimed to assess the safety and tolerability of the immune checkpoint inhibitor nivolumab, as monotherapy or combined with chemotherapy, in Japanese patients with biliary tract cancer. Methods: This multicentre, open-label, phase 1 trial was done at four cancer centres in Japan. Eligible patients were aged 20–79 years, had biliary tract adenocarcinoma (intrahepatic bile duct cancer, extrahepatic bile duct cancer, gallbladder cancer, or ampullary cancer), Eastern Cooperative Oncology Group performance status 0 or 1, adequate hepatic, renal, and haematological function, and tumour tissue samples for PD-L1 expression analysis. Patients with unresectable or recurrent biliary tract cancer that was refractory or intolerant to gemcitabine-based treatment regimens received nivolumab monotherapy (240 mg every 2 weeks [monotherapy cohort]). Chemotherapy-naive patients with unresectable or recurrent biliary tract cancer received nivolumab (240 mg every 2 weeks) and cisplatin (25 mg/m 2 ) plus gemcitabine (1000 mg/m 2 ) chemotherapy (combined therapy cohort). The primary objective was to assess tolerability and safety. The primary objective was assessed in the safety population of all patients who had received at least one dose of nivolumab. This study is registered withwww.clinicaltrials.jp, number JapicCTI-153098, and follow-up is ongoing. Findings: 30 patients were enrolled into each cohort between Jan 13, 2016, and April 19, 2017. Data cutoff was Aug 31, 2017. In the monotherapy cohort, the most frequently reported treatment-related adverse events were decreased appetite (five [17%]), malaise (four [13%]), and pruritus (four [13%]). Grade 3–4 treatment-related adverse events were reported by three (10%) patients (rash, maculopapular rash, and amylase increase) and treatment-related serious adverse events were reported by one (3%) patient (pleurisy). In the combined therapy cohort, the most frequently reported treatment-related adverse events were neutrophil count decrease (any grade 25 [83%]; grade 3–4 in 23 [77%] patients) and platelet count decrease (any grade 25 [83%] of 30; grade 3–4 in 15 [50%] patients). Six (20%) patients reported 11 treatment-related serious adverse events (platelet count decrease [three patients], febrile neutropenia [two patients], neutrophil count decrease, anaemia, anaphylactic reaction, decreased appetite, pyrexia, and myocarditis [one patient each]). In the monotherapy cohort, median overall survival was 5·2 months (90% CI 4·5–8·7), median progression-free survival was 1·4 months (90% CI 1·4–1·4), and one of 30 patients had an objective response. In the combined therapy cohort, median overall survival was 15·4 months (90% CI 11·8–not estimable), median progression-free survival was 4·2 months (90% CI 2·8–5·6), and 11 of 30 patients had an objective response. Interpretation: Nivolumab had a manageable safety profile and signs of clinical activity in patients with unresectable or recurrent biliary tract cancer. This initial assessment of nivolumab for the treatment of advanced biliary tract cancer provides supportive evidence for future larger randomised studies of nivolumab in this difficult to treat cancer. Funding: Ono Pharmaceutical Co Ltd and Bristol-Myers Squibb Inc.